Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest)--Dungeness crab - Pauley, Gilbert B.; Armstrong, David A.; Heun, Thomas W. (Washington U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.63)
Keywords: Invertebrates; Fishes; History; Dungeness crab